Benefits of Red Wine -A Review - ELANGKOVAN, DENESH RAJ; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
The healthful and nutritive properties of wine have been acknowledged for thousands of years. Moderate consumption of red wine on a regular basis may be preventative against coronary disease. Moderate wine consumption with reduced mortality, mostly due to reduced incidence cardiovascular disease. Diet rich in fruit and vegetables, together with moderate amounts of alcohol, but more specific red wine in moderation, is protective against various degenerative diseases. Variety of mechanisms that target all the crucial steps of atherosclerosis, from early formation of the atherosclerotic plaque to its life-threatening complications (ulceration, thrombosis, vessel occlusion and infarction). These effects are attributable to the synergic properties of several biochemical components of wine (alcohol, resveratrol, and especially polyphenol compounds), particularly the red varieties. Laboratory evidence to promote the consumption of grapes and wine as part of a balanced diet and lifestyle certain individuals to prevent cardiovascular disease. The presence of salicylic acid and other phenolic compounds that provide protection against platelet aggregation y altering eicosanoid metabolism in favour of increased prostacyclin and decreased thromboxane A.